Synthesis and characterization of Zn3Nb2O8nanopowders via a rapid vibro-milling technique - P. Pakawanit (2018)
The simple mixed-oxide method via a rapid vibro-milling technique is explored in the preparation of pure zinc niobate (Zn 3 Nb 2 O 8 ) nanopowders. The formation of the phase in the calcined powders has been investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM/TEM and EDX techniques. It has been found that the minor phase of ZnNb 2 O 6 tends to form together with the Zn 3 Nb 2 O 8 phase, depending on calcination conditions. More importantly, it is seen that optimization of calcination conditions can lead to a single-phase Zn 3 Nb 2 O 8 in a monoclinic phase. © 2013 Copyright Taylor and Francis Group, LLC.